The ‘Expected Leadership’ in Indonesia’s Initiative to Form ASEAN Peacekeeping Centres Network - Farhan Julianto (Jurnal Hubungan Internasional, 2023)
Various International Relations works of literature positioned Indonesia as one of the leading countries in Southeast Asia, both formally and informally. Indonesia is considered a driving force behind various regional cooperations that lead to regional progress. This paper also sees that Indonesia is capable of initiating and pushing for cooperation in the peacekeeping area. Peacekeeping cooperation is sensitive in Southeast Asia, considering that one of the norms that mutually agreed upon since the formation of ASEAN is the norm of non-interference. The non-interference norms hinder regional peacekeeping cooperation due to its adoption of interventionist norms. Despite these organizational obstacles, Indonesia has successfully initiated peacekeeping cooperation that in the form of the ASEAN Peacekeeping Centres Network (APCN). The APCN aims to increase the contribution of peacekeeping forces from the ASEAN Member States in the UN Peacekeeping Missions. By looking at the case, this paper aims to explain why Indonesia was successful in initiating the APCN when the regional norm of non-interference is still adopted. This explanation will refer to the role theory, first theorized in International Relations by Kaleevi Jakko Holsti. Although the initiation of the APCN was also driven by foreign policy aspirations from the policymakers, another contributing factor was the regional expectations for Indonesia to lead the regional peacekeeping cooperation. This expectation is in line with Holsti’s concept of role prescription. Further understanding of the expected leadership could be an alternative perspective in seeing the success or failure cases of regional cooperation – especially in Southeast Asia – in the future.